2007
DOI: 10.1136/emj.2007.047993
|View full text |Cite
|
Sign up to set email alerts
|

Parental weight estimation of their child's weight is more accurate than other weight estimation methods for determining children's weight in an emergency department?

Abstract: Objective: To compare the various paediatric weight estimation methods (Advanced Pediatric Life Support, Broselow Tape, Argall, and Best Guess) and parental estimate to measured weight. Patients and method: A convenience sample of children aged 1-11 years who presented to the emergency department over a 6 month period were eligible for inclusion. Data collected included height, age, ethnicity, parent estimate of weight and measured weight. Body mass index (BMI) was calculated. The outcome of interest was agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 13 publications
5
67
1
4
Order By: Relevance
“…When it was compared with other estimations, parental estimation performed better than Broselow Luten tape in all weight categories. Krieser et al 25 also previosuly reported that parental estimation of the weight was more accurate than Broselow Luten tape. However, Broselow Luten tape performed better than physician and nurse estimates in all weight categories, consistent with the study of Rosenberg et al 8 in which physician estimations was worse than Broselow Luten tape except in obese patients, yet obese patients were not included in our study group.…”
Section: Discussionmentioning
confidence: 97%
“…When it was compared with other estimations, parental estimation performed better than Broselow Luten tape in all weight categories. Krieser et al 25 also previosuly reported that parental estimation of the weight was more accurate than Broselow Luten tape. However, Broselow Luten tape performed better than physician and nurse estimates in all weight categories, consistent with the study of Rosenberg et al 8 in which physician estimations was worse than Broselow Luten tape except in obese patients, yet obese patients were not included in our study group.…”
Section: Discussionmentioning
confidence: 97%
“…This finding most likely reflects the lower priority accorded to anthropometric (93) 7 (5) 1 (1) 91 (65) 18 (13) 1 (1) 17 (12) 12 (9) 34 (24) 5 (4) 101 (73) 13 (9) 6 (4) 7 (5) 99 ( (89) 6 (5) 1 (1) 79 (66) 13 (11) 4 (3) 17 (14) 6 (5) 22 (18) 7 (6) 83 (70) 0 (0) 1 (1) 15 (13) 110 ( www.ajcconline.org measurements compared with other time-sensitive and effort-intensive critical interventions necessary to stabilize a child upon admission to the PICU. Reports 4,[11][12][13] indicate that estimates of anthropometric measurements by a patient's parent or caregiver or by PICU staff are erroneous, often by wide margins. Although records from referring hospitals or outpatient clinic visits are an additional source of information, the weight, stature, and head circumference listed in those records may also have been estimates made by a patient's parent or caregiver or by health care providers.…”
Section: Discussionmentioning
confidence: 99%
“…Weight that is not measured is often determined, with various degrees of accuracy, on the basis of estimates made by the clinical care team or a patient's parents. 4,[11][12][13] Stature and head circumference are often not measured, perhaps because of a perceived lack of importance in the list of priorities during care of a critically ill infant or child. The lack of accurate and consistent anthropometric data can thus pose marked risks to the safe management and recovery of a critically ill child and, in some instances, result in harm.…”
mentioning
confidence: 99%
“…The patient's weight must then be estimated to calculate medication dosages or other needs. There are a number of methods currently used to estimate a child's weight such as visual assessment, parental estimation [3,4], an age formula [5,6], and lengthbased estimations such as that using the Broselow tape [7][8][9][10][11][12][13][14][15][16].…”
Section: Brief Communication (Original)mentioning
confidence: 99%